The Books behind the Masks : Sources of Warfare Leadership in Ancient Egypt. Ancient Warfare Series Volume 4 - Spalinger, Anthony (Culture and History of the Ancient Near East, 2022)
The study of the ancient Egyptian military and warfare now encompasses the background court society in which the various eulogies drawn up for the glorification of the kings were composed. This study proceeds from a previous analysis of the leadership characteristics of the military pharaohs to their underlying war records to the literary compositions that the pharaohs had drawn up for their glorification. A study of these court-inspired accounts fits within the overarching new perspectives of royally directed and inspired ancient Egyptian literature. The historical background covers the New Kingdom pharaohs Kamose, Thutmose III, Ramesses II and III, with Merenptah, plus Pianchy. The concentration is primarily upon the narrative structures employed in each of these king's monumental inscriptions.